Transaction involving wealth that mixed between lawful and unlawful under Islamic law and its application in Islamic banking and practice - Hj Ibrahim, Badruddin (2015)
This study examines the issue of transaction involving wealth that mixed between lawful and unlawful or in other words legal and illegal under Islamic law and its application in Islamic Banking. The question is whether it is allowed to make a transaction with the possessor of mixed wealth (lawful and unlawful) in various kinds of transaction such as deposit taking, investment, sale, partnership and so forth. This is applicable in case if the party to the transaction has acknowledge that some wealth of another party comes from unlawful sources like interest (riba), gambling, prostitution, trading of human being or trading of prohibited items, etc. The discussion focusses on concept of lawful and unlawful wealth, the meaning of mixed wealth, and the position of Islamic law regarding the dealing involving mixed wealth between lawful and unlawful. The discussion also examines the current banking practices particularly in Malaysia on transaction involving wealth that mixed between lawful and unlawful. Examination on such issues will be based on the perspective of the Qura’an and the Sunnah as primary sources of Islamic law. It is then followed with the analysis of the view of Muslim jurist of four well known schools of law (Hanafis, Malikis, Shafi’is, and Hanbalis) as well as the view of contemporary Muslim scholars. In addition, the reference also will be made to legal opinions (fatawa) from some renowned Muslim scholars. The study will finally provide a clear guideline regarding the transaction involving mixed wealth and henceforth can be used as reference either by individual person or institution in this day.